2018
DOI: 10.1111/tbed.12812
|View full text |Cite
|
Sign up to set email alerts
|

Duck “beak atrophy and dwarfism syndrome” disease complex: Interplay of novel goose parvovirus-related virus and duck circovirus?

Abstract: As a newly emerged infectious disease, duck "beak atrophy and dwarfism syndrome (BADS)" disease has caused huge economic losses to waterfowl industry in China since 2015. Novel goose parvovirus-related virus (NGPV) is believed the main pathogen of BADS disease; however, BADS is rarely reproduced by infecting ducks with NGPV alone. As avian circovirus infection causes clinical symptoms similar to BADS, duck circovirus (DuCV) is suspected the minor pathogen of BADS disease. In this study, an investigation was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 31 publications
1
30
1
Order By: Relevance
“…Based on these results, we confirmed that among these 19 DuCVs, Group 1 was prevalent in Guangdong, Group 2 was prevalent in Guangxi and both groups were prevalent in Yunnan province. Interestingly, there were differences between the DuCVs identified in this study and other DuCVs from previous reports, and the genome lengths of the novel sequences GD150501, GD150502 GD180503, GD180504, GD190401, GD190402 and GD190403 were all 1987 nt, which is the shortest observed DuCV genome on record [15,20,24,26]. When the sequences were compared with the other genomes in GenBank, it became clear that there was a deletion at the 966 site in the intragenic region in 7 DuCVs from Guangdong, and other DuCVs also showed multiple Fig.…”
Section: Discussioncontrasting
confidence: 45%
See 3 more Smart Citations
“…Based on these results, we confirmed that among these 19 DuCVs, Group 1 was prevalent in Guangdong, Group 2 was prevalent in Guangxi and both groups were prevalent in Yunnan province. Interestingly, there were differences between the DuCVs identified in this study and other DuCVs from previous reports, and the genome lengths of the novel sequences GD150501, GD150502 GD180503, GD180504, GD190401, GD190402 and GD190403 were all 1987 nt, which is the shortest observed DuCV genome on record [15,20,24,26]. When the sequences were compared with the other genomes in GenBank, it became clear that there was a deletion at the 966 site in the intragenic region in 7 DuCVs from Guangdong, and other DuCVs also showed multiple Fig.…”
Section: Discussioncontrasting
confidence: 45%
“…The novel DuCVs can infect different breeds of ducks, and ducks over 4 weeks old were the most susceptible. We were the first to report variations in the complete genome lengths of and recombination in a novel DuCV in southern and southwestern China [15,20,[24][25][26]. DuCVs in additional species of ducks remain to be detected, and no wild bird samples were collected.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DuCV often coinfects with other bacterial and viral pathogens ( Hattermann et al., 2003 ; Ball et al., 2004 ; Soike et al., 2004 ; Jiang et al., 2008 ; Zhang et al., 2009 ). Our previous report suggested that the coinfection of NGPV and DuCV might aggravate the development of the BADS disease in Cherry Valley ducks and mule ducks ( Li et al., 2018b ).…”
Section: Introductionmentioning
confidence: 99%